PRECISION MEDICINE: CUSTOMIZED HAEMATOLOGICAL REFERENCE INTERVALS FOR NAKURU COUNTY'S DIVERSE POPULATION - Gichuru, Alice Wanjiku (American Journal of Public Health and Epidemiology (AJPHE), 2023)
Haematology reference intervals play a crucial role in clinical laboratory systems, serving as the cornerstone for healthcare provision and diagnostic procedures. This paper explores the significance of reference hematological parameters in disease screening, diagnosis, and the detection of blood disorders. The establishment of these reference intervals involves utilizing blood specimens and assigning values obtained from research studies to specific intervals. These intervals encompass the upper and lower reference limits, typically defined at the 95% confidence level. The comprehensive understanding of haematological reference intervals is vital for ensuring accurate and effective healthcare management